An overview of immunization practices in Pakistan (International Current Pharmaceutical Journal, 2016)
Effective immunization practices are invariably a big challenge for Pakistan, facing many problems and barriers to immunize children against vaccine preventable diseases. Immunization coverage in Pakistan requires up-gradation. Barriers in attaining immunization goals are lack of Parents acceptance, lack of Parents awareness and knowledge about benefits of vaccination, socioeconomic inequity and lack of security for vaccinators. The problems of vaccine procurement are its transportation, storage and administration which also contribute to errors of immunization practices. In Pakistan Expanded Program on Immunization (EPI) with the support of WHO & UNICEF has a significant impact on overcoming these barriers. Expanded Program on Immunization (EPI) is facilitating through many vaccination centers, mobile vaccination sessions and public awareness campaigns, health visitors and EPI trained vaccinators to eradicate the barriers towards poor immunization practices in Pakistan. It is concluded from this study that it is the responsibility of Government and Health Professionals to find solutions to increases vaccination rate and coverage. It is the need of hour to find ways for creating awareness among parents and motivate them to follow complete vaccination schedule for the sake of better child health.Wain et al., International Current Pharmaceutical Journal, October 2016, 5(11): 94-96http://www.icpjonline.com/documents/Vol5Issue11/01.pdf